Exploring the Combination of Language, Images and Sound in the Metaphors of tv Commercials - Caballero, Rosario (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2014)
Drawing into research on multimodal metaphor, the first objective of this paper is to provide an analysis of the multimodal metaphors in four commercials selling alcoholic drinks, cars and computers to illustrate ways in which metaphor may be instantiated via sound, image and language. The question addressed is whether the metaphorical rendering of these products results from combining several communicative modes or rather relies mainly on one mode on which the others depend. Based on the results of a questionnaire completed by sixty informants after watching the commercials, the second objective is to explore the way viewers react to, and interpret, multimodal metaphors in advertising discourse.